Kajian Usahatani Cabai Rawit di Desa Dawi-Dawi, Kecamatan Wonggeduku, Kabupaten Konawe - Alfianti Alfianti; Milawati Saranani; Leni Saleh (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The purpose of the study was to analyze the study of Chili Pepper Farming and Farmer Income in Dawi-Dawi Village, Wonggeduku District, Konawe Regency. The sampling method used in this study was the census method. The census method is a method that takes one population group as a sample as a whole and uses a structured questionnaire as the main data collection tool to obtain specific information, where the respondents are all farmers who have been sampled in this study. so that the number of samples in this study was 10 people. To solve the research problem, namely by using a qualitative descriptive method. The agribusiness system of Chili Pepper farming production in Dawi-Dawi Village, Wonggeduku District consists of upstream to downstream subsystems. The upstream subsystem is the procurement of production facilities such as seeds, fertilizers, medicines, while the tools used are simple and modern tools, namely machetes, hoes, machetes, sprayers, sickles and chopping machines, all production facilities and tools are purchased at farmer shops and agricultural equipment stores. On-farm substem/cayenne pepper cultivation in Dawi-Dawi Village starts from land preparation, planting, fertilizing, weeding/replanting, pest control and harvesting. While the downstream/marketing subsystem, cayenne pepper farmers sell their production directly to middlemen at a price of Rp 55,000 per kilogram.